KEMANDIRIAN BELAJAR MAHASISWA PENDIDlKAN TEKNIK MESIN DITINJAU DAR! ASAL SEKOLAH, TEMPAT TINGGAL, DAN LAMA STUDI - Pardjono, Pardjono (Jurnal Cakrawala Pendidikan, 2016)
he system employing semester credit units requires students’ good self-regulated learning in order that they attain learning goals successfully. The present article concerns a research aimed at knowing (l) of what level mechanical engineering students’ self dependence in learning was as seen from both their self-stated views about their self-regulated learning and their self-regulated learning in practice; (2) whether there was any difference in level of self regulated learning among those having different types of high school educational background; (3) whether there was any difference in level of self-regulated learning among those having studied for different numbers of semesters; and (4) whether the environment where they live influences their self-dependence in learning, or, in other words, their self-regulated learning. The research employed a positivistic approach which was exploratory in nature. The population consisted of 254 students of the Mechanical Engineering Education Study Program, Faculty of Engineering, State University of Yogyakarta, who were taking courses in one even-numbered semester or another in the academic year of 2005/2006. The sample size was 228 and the research subjects were randomly selected. The data were compiled by using a closed self-report type of questionnaire using a Linkert-type scale model. The data were analyzed by means of non-parametric statistics using the Kruskal-Wallis Test and the Mann-Whitney U Test since the data distribution did not fulfill the inferential parametric analysis assumption The research findings indicate that (1) the level of the students’ self-regulated learning was very good though the mean score for their self-regulated learning in practice is lower than that for their self-stated views about their self-regulated learning; (2) there is no difference in level of self-regulated learning between those with a general high school educational background and those with a vocational high school educational background, according to both their self-stated views on it and their self-regulated learning in practice; (3) there is no difference in level of self-regulated learning between those who live with their family and those who live at some off-campus housing, according to both their self-stated views on it and their self-regulated learning in practice; and (4) there is no difference in level of self-regulated learning among those having studied for different numbers of semesters, according to both their self-stated views on it and their self-regulated learning in practice, excluding the views of those in their second semester on their self regulated learning